Analysis of HIV/AIDS Health Problems in Pacitan District East Java 2020 - Famil, Mohamad (Institute of Topical Disease Universitas Airlangga, 2021)
The implementation of health problem analysis is carried out to increase the eff ectiveness and effi ciency of solving health problems through the selection of health problems that become priority problems in a region. The purpose of this study was to analyze the problem and determine the priority of health problems in the work area of the Pacitan District Health Office, East Java Province. This research is a descriptive observational study conducted at the Pacitan District Health Office in January 2020. The type of data used is secondary data obtained from the 2016-2019 Pacitan District Health Profile and primary data obtained through interviews with related parties, namely the head of the fi eld. , section head and program holder. Prioritization of health problems is carried out using the USG method based on the criteria of Urgency, Seriousness, Growth and fi nding the root of the problem using the fi shbone diagram method. The increase in HIV/AIDS cases with an USG score of 128 has become a top priority health problem in Pacitan District. An increase over the last 4 years with the highest number of cases in 2019, which was 39 cases. The fishbine diagram shows the root of the HIV/AIDS problem, namely the lack of public knowledge about HIV/AIDS, the lack of public knowledge about HIV/AIDS, the lack of awareness of people at risk for conducting an HIV test, this makes the community less aware of information about HIV/AIDS, causing public stigma. which results in people being closed / unwilling to check themselves at the puskesmas orhospital. The increase in HIV/AIDS cases is one of the problems in Pacitan district. To reduce the incidence, health workers need to optimize the dissemination of information about HIV/AIDS, especially risk factors, causes, prevention, symptoms and treatment. Increase the understanding of health workers and public awareness in conducting early detection.